Masculinidade e feminicídio: uma leitura psicanalítica - Silva, Nei Paulino da (2021)
Men are protagonists of the different forms of violence practiced against women, a reality that shows the importance of studies on the psychic aspects that involve these relationships, especially in societies founded on patriarchy. In general terms, the path taken in this dissertation was based on psychoanalytic theory and aimed to analyze the possible connections between models of masculinity in contemporary culture and crimes of femicide, taking excerpts from judicial processes of femicide crimes as an elucidative resource of proposed discussions. The research findings signaled that contemporary masculinity is still supported by the misogynist perspective and the encounter with feminine aspects is unbearable. The work of inventing new ways of being a man seems to consist in enduring the distressing encounter with femininity – lack, passivity and vulnerability – an experience that takes place in the encounter with the Real. This experience allows the subject to realize that there are no signs that can plug the subject's structural hole or completely eradicate anxiety.